2017
DOI: 10.3389/fphar.2017.00488
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Divergent Clinical Outcomes and Precision Medicine: An Important New Role for Institutional Review Boards and Research Ethics Committees

Abstract: The efforts toward individualized medicine have constantly increased in an attempt to improve treatment options. These efforts have led to the development of small molecules which target specific molecular pathways involved in cancer progression. We have reviewed preclinical studies of sunitinib that incorporate sex as a covariate to explore possible sex-based differences in pharmacokinetics and drug–drug interactions (DDI) to attempt a relationship with published clinical outputs. We observed that covariate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 108 publications
1
15
0
Order By: Relevance
“…Furthermore, a subanalysis in a randomised trial of prophylactic indomethacin showed that the intervention reduced the rate of severe IVH in boys more than in girls 43. Future studies should similarly perform sex-differentiated data analysis to identify differential treatment effects between boys and girls 28. If sex is found to modulate the clinical outcomes of a treatment, then patient management may hypothetically be adjusted individually and tenets of precision medicine can be realised.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a subanalysis in a randomised trial of prophylactic indomethacin showed that the intervention reduced the rate of severe IVH in boys more than in girls 43. Future studies should similarly perform sex-differentiated data analysis to identify differential treatment effects between boys and girls 28. If sex is found to modulate the clinical outcomes of a treatment, then patient management may hypothetically be adjusted individually and tenets of precision medicine can be realised.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of longitudinal trends in sex-specific care practices, mortality and major morbidities among preterm neonates is important for counselling families, optimising existing interventions and personalising interventions in a sex-specific manner to improve outcomes, which is a concept highlighted as precision medicine 28. Our objective was to investigate the differences in outcomes of preterm boys and girls born at <29 weeks’ gestation and evaluate the trend of rate differences to identify any change over 10 years.…”
mentioning
confidence: 99%
“…This policy is not a mandate to specifically investigate sex differences, but requires investigators to consider sex from the design of the research question through reporting the results (Clayton, ). In some instances, sex might not influence the outcomes (e.g., Fritz, Amrein, & Wolfer, ; Segarra, Modamio, Fernandez, & Marino, ), but balancing sex in animal and cellular models will distinctly inform the various levels of research (Clayton, ). More specific guidelines for applying the policy of considering sex as a biological variable are also available (Clayton, ; McCarthy, Woolley, & Arnold, ), but shifting the experimental group composition should be done in the context of appropriate a priori power analyses.…”
Section: Reporting Criteria To Ensure Rigor and Transparencymentioning
confidence: 99%
“…Several of the articles call for more comparison of research findings by sex, noting that, like race and ethnicity, sex differences in many domains are still widely understudied. [56][57][58][59][60] Regardless of actual representation of females in biomedical research, many health outcomes specific to them will remain unknown unless researchers prioritize exploring differences across sex assigned at birth, race, and ethnicity. In addition, sex is predominantly perceived as a binary biological construct and individuals born as intersex, or those with disorders of sexual development, have difficulties "fitting" into a male/female binary category.…”
Section: Plos Onementioning
confidence: 99%